Bilateral ocular surface squamous neoplasia: A study of 25 patients and review of literature. Issue 1 (January 2022) - Vempuluru, Vijitha S; Pattnaik, Monalisha; Ghose, Neha; Kaliki, Swathi
Purpose: To describe the risk factors, clinical presentation, management, and outcomes of patients with bilateral ocular surface squamous neoplasia (OSSN). Methods: Retrospective case series. Results: Of the 25 patients with bilateral OSSN, the mean age at diagnosis of OSSN was 31 years (median, 24 years; range, 2–60 years). Risk factors for bilateral OSSN included xeroderma pigmentosum ( n  = 15, 60%), human immunodeficiency virus infection ( n  = 3, 12%), conjunctival xerosis ( n  = 1, 4%), and topical steroid use ( n  = 1, 4%). There were no identifiable ocular or systemic risk factors in 7 (28%) patients. Presentation was synchronous in 14 (56%) and metachronous in 11 (44%) patients. Tumor morphology was bilaterally similar in 12 (48%) patients. Histopathological examination ( n  = 36) revealed conjunctival intraepithelial neoplasia (CIN) grade 1 in 4 (8%); grade 2 in 7 (14%); carcinoma in situ in 5 (10%), and invasive carcinoma in 20 (40%). Primary management of OSSN ( n  = 49) included excisional biopsy ( n  = 31, 62%), topical immunotherapy (IFN α2B) ( n  = 11; 22%), topical Mitomycin C (MMC) ( n  = 3, 6%), enucleation ( n  = 1, 2%), orbital exenteration ( n  = 2, 4%), and plaque brachytherapy (PBT) ( n  = 1, 2%). One patient was lost to follow-up after detection of tumor in the second eye. Recurrent tumors were noted in 16 (32%) eyes and binocular globe salvage was achieved in 16 (64%) patients at a mean follow up of 41 months (median 30 months; range, 1–164 months). Conclusion: OSSN occurrence can be synchronous or metachronous. Meticulous examination of the fellow eye is important for an early diagnosis of OSSN.